Penerapan akhlak terpuji pada tingkat SD/MI dengan menggunakan media non-digital (diorama) - Reihan, Alifia Nur (Maliki Interdisciplinary Journal, 2025)
The cultivation of praiseworthy morals in primary level students is a fundamental aspect of character education. One of the learning strategies that can be used is the utilization of non-digital media, one of which is diorama. This study aims to describe the application of diorama media in learning praiseworthy morals in SD / MI and assess its effectiveness in instilling character values. The research used the Research and Development (R&D) approach with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fourth and fifth grade students in two Islamic elementary schools in Malang Regency. The results showed that the diorama made a positive contribution to the improvement of students' understanding, involvement, and moral behavior in everyday life. Through this media, students can actively observe, discuss, and emulate the moral behavior displayed in three-dimensional form, which makes it more contextual and meaningful.